Percutaneous Transhepatic Biopsy for Extrahepatic Lesions - Onishi, Yasuyuki; Arai, Yasuaki; Sone, Miyuki; Sugawara, Shunsuke; Itou, Chihiro; Kimura, Shintaro (The Arab Journal of Interventional Radiology, 2021)
Purpose The purpose was to assess the diagnostic accuracy and safety of percutaneous transhepatic biopsy for extrahepatic lesions.Materials and Methods Between January 2008 and December 2019, 26 patients (17 men and 9 women; median age, 60 years) underwent percutaneous transhepatic needle biopsy for extrahepatic lesions at our institution. Transhepatic biopsy was deemed appropriate compared with other biopsy routes or methods (i.e., endoscopic or surgical). The lesions were in the porta hepatis (n = 9), retroperitoneum (n = 6), right adrenal gland (n = 4), right kidney (n = 3), lesser omentum (n = 2), duodenum (n = 1), pleura (n = 1), and inferior vena cava (n = 1). The median maximal diameter of the lesions was 45.5 mm (range, 18–148 mm). Core-needle biopsy was performed in all patients. Eighteen-gauge and 21-G needles were used in 25 and one patient, respectively. Ultrasound was used for biopsy in 21 patients, and CT fluoroscopy was used in five patients. Postbiopsy tract embolization was performed in three patients. Technical success and diagnostic accuracy of the biopsy were evaluated. Complications were recorded using the systemic inflammation response (SIR) criteria.Results The pathological results of biopsy were carcinoma (n = 10), lymphoma (n = 9), and other diagnoses (n = 7). Technical success was obtained in all patients. The accurate diagnosis was achieved in 24 of the 26 patients (92.3%). A major complication, a bladder tamponade, was observed in one patient (3.8%) after biopsy of a right kidney lesion. A hematoma caused by iatrogenic renal injury likely obstructed the bladder outlet. Minor complications were observed in three patients (11.5%).Conclusions Percutaneous transhepatic biopsy for extrahepatic lesions is feasible with acceptable safety.
Keywords: nonvascular intervention; percutaneous needle biopsy; transhepatic biopsy